Analisis Kinerja Perusahaan Berdasarkan Rasio Keuangan Pada Laporan Keuangan PT Gozco Plantations Tbk Periode 2020-2022 - Syawalinda, Rara Nagita; Pratiwi, Anne Shofia (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study aims to analyze the financial performance of PT Gozco Plantations Tbk for the period 2020-2022. This analysis uses the financial ratio method to evaluate a company's performance, which covers the ratio of liquidity, solvency, and profitability. The information used comes from the annual reports published by the company. The research results showed that PT Gozco Plantations Tbk experienced performance changes during the period. In 2020, the company's profitability experienced a significant decline due to the impact of the COVID-19 pandemic, but by 2021 and 2022, most economic indicators have improved. A stable ratio of liquidity and solvency shows the company's ability to meet its short- and long-term obligations. This research provides an overview of the factors that influence financial performance and its impact on stakeholders of PT Gozco Plantations Tbk.